2021
DOI: 10.29121/granthaalayah.v9.i5.2021.3933
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Leadership Styles in Public and Private Secondary Schools in Ido Local Government Area of Ibadan, Oyo State

Abstract: This study compared the leadership styles of principals dominating in both public and private secondary schools in Ido Local Government Area of Ibadan, Oyo State, and also investigated the principals’ gender differences. Leadership styles examined include: autocratic, visionary, , democratic, coaching, servant, , , , bureaucratic and digital. A descriptive research design was adopted. The population of the study consists of 26 public secondary schools and 97 registered private secondary schools. The total popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Awodiji et al's (2019) study revealed that transformational leadership are the most used leadership approach by public secondary school principals in Oyo Metropolis public secondary schools, Oyo State. Bakare and Oredein (2023) revealed from teachers' perspectives that the laissez-faire leadership style is the most adopted leadership style among senior secondary school principals in Ibadan Metropolis while the principals' perspectives revealed the digital leadership style is being widely practised among senior secondary schools' principals in Ibadan Metropolis Oyo State.…”
Section: Results and Discussion Current State Of Transformational Lea...mentioning
confidence: 99%
“…Awodiji et al's (2019) study revealed that transformational leadership are the most used leadership approach by public secondary school principals in Oyo Metropolis public secondary schools, Oyo State. Bakare and Oredein (2023) revealed from teachers' perspectives that the laissez-faire leadership style is the most adopted leadership style among senior secondary school principals in Ibadan Metropolis while the principals' perspectives revealed the digital leadership style is being widely practised among senior secondary schools' principals in Ibadan Metropolis Oyo State.…”
Section: Results and Discussion Current State Of Transformational Lea...mentioning
confidence: 99%